PENGARUH KEPUASAN PELANGGAN DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN - Febrianto Febrianto; Eti Arini (Yayasan Insani Mandiri Santani, 2022)
Customer loyalty is the loyalty of consumers to a product/service. Several factors that influence customer loyalty are customer satisfaction and customer trust. This study aims to determine the effect of customer satisfaction and customer trust on customer loyalty for drinking water in the KitaRO brand at the Putra Kitaro agent, Manna City, South Bengkulu. This type of research is quantitative research with a descriptive approach. The population of this study were all customers of KitaRO branded bottled water at the Putra KitaRO agent, Manna City, South Bengkulu. The number of research samples as many as 120 people. Data collection was done by observation and questionnaires. The data analysis technique used multiple linear regression analysis techniques. The results of data analysis obtained multiple linear regression equations as follows: Y = 2.251 + 0.281 X1 + 0.621 X2. The results of the analysis show that partially customer satisfaction has a positive and significant effect on customer loyalty (tcount = 4.774 and tsig = 0.000) and customer trust has a positive and significant effect on customer loyalty (tcount = 6.793 and tsig = 0.000). Simultaneously there is an effect of customer satisfaction and customer trust on customer loyalty (Fcount = 82,464 and Fsig = 0.000). It is recommended to Putra KitaRO agents to be able to increase customer loyalty by creating customer satisfaction and high customer trust in drinking water products in the KitaRO brand packaging. Keywords: Loyalty, Satisfaction, Trust